2017
DOI: 10.1007/978-3-319-65091-3
|View full text |Cite
|
Sign up to set email alerts
|

Cross Cultural Issues in Consumer Science and Consumer Psychology

Abstract: Regardless of whether the research goal is to establish cultural universals or to identify and explain cross-cultural differences, researchers need measures that are comparable across different cultures when conducting cross-cultural studies. In this chapter we describe two major strategies for enhancing cross-cultural comparability. First, we discuss a priori methods to ensure the comparability of data in cross-cultural surveys. In particular, we review findings on cross-cultural differences based on the psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Likewise, the GLOBE model suggested that cultural values serve as the locus points and people make decisions based on the perceived similarity of the behavior in question [39]. In verily, these theories affirmed that the congruency of ad appeals (verbal or non-verbal cues) are expected to cause a consumer to be attracted to culturally convergent advertising, leading toward self-affirmation [40]. Additionally, these culturally convergent ad appeals are expected to be trusted as socially accepted concerning the adoption of the advertised product or brand as liked.…”
Section: Literature Review 21 Research Gap and Theoretical Underpinmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, the GLOBE model suggested that cultural values serve as the locus points and people make decisions based on the perceived similarity of the behavior in question [39]. In verily, these theories affirmed that the congruency of ad appeals (verbal or non-verbal cues) are expected to cause a consumer to be attracted to culturally convergent advertising, leading toward self-affirmation [40]. Additionally, these culturally convergent ad appeals are expected to be trusted as socially accepted concerning the adoption of the advertised product or brand as liked.…”
Section: Literature Review 21 Research Gap and Theoretical Underpinmentioning
confidence: 99%
“…There are two facets of cultural variables that must be well thought out in advertising research. First, is the study interested in learning about the desirable (what people should do) or the desired (what people want to do) [40,42]? Usually, the answers to the questions of what an individual does and what one thinks should be done are inversely correlated.…”
Section: Literature Review 21 Research Gap and Theoretical Underpinmentioning
confidence: 99%